2018
DOI: 10.4028/www.scientific.net/ssp.284.1063
|View full text |Cite
|
Sign up to set email alerts
|

Portland Cement with Mineral Fillers and Polymer Additives

Abstract: This paper is devoted to the study of the hardening process and the mechanical properties of composite cements. There were three mineral additions and two polymer ones, namely fly ash, limestone meal and marble powder, polymer dispersion and redispersible polymer powder used. The principal possibility of combining mineral fillers in the design of composite cements is shown. It has been established that the samples of cement stone based on binders modified with redispersible polymer powder have higher compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This is due to the dispersion of this material, the cubiform shape of its grains and their smooth and relatively flat surface. This effect is confirmed by other studies [1][2]7]. After forming and hardening cement stone in the desiccator the density and strength of stone were determined (Table 2, Fig.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is due to the dispersion of this material, the cubiform shape of its grains and their smooth and relatively flat surface. This effect is confirmed by other studies [1][2]7]. After forming and hardening cement stone in the desiccator the density and strength of stone were determined (Table 2, Fig.…”
Section: Resultssupporting
confidence: 83%
“…It can be achieved by several technological methods: careful selection of granulometric composition of bulk components; introduction of chemical additives that reduce the porosity of the composite; introduction of active mineral additives that are able to react with Portland cement minerals and directed to change the mineralogical composition of the hardened stone. Also an effective way of compacting the structure of cement composites is the use of fine mineral fillers [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…without additions it is possible to draw a conclusion about some plasticizing action of dust particles which are present in sand. We have seen this effect in our other studies [12]. Also it was found that Power floor 1130 addition in an amount of 0.8 % and Powerfloor 3100 additive in an amount of 0.2 % are the most effective as plasticizer of concrete mix based on selected materials.…”
Section: Th Concrete Dayssupporting
confidence: 58%
“…[ 3 , 4 ]. The most common polymer modifiers for DBM are re-dispersible polymer powders (RP) [ 5 , 6 , 7 , 8 ], which are prepared by emulsion polymerization or copolymerization of polymers in the dispersion state; after further spraying and drying methods, they are able to create a dispersion in water (re-dispersible) [ 9 ]. After mixing the RP with water it is instantly and completely re-dispersed, and disperse particles combine and form films with tensile strength for nearly 4.9 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they can be used to increase the homogeneity of the hardened mortar, increase the bond strength, compressive and tensile strength under bending, deformation property, water absorption, frost resistance, etc. [ 3 , 5 , 7 ]. Cellulose ethers are effective additives to increase the water-holding properties of dry building mixtures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%